Cavitation of superplastic alloys: a study using a hot microhardness technique - Sohal, Gurnam Singh (Cranfield University, 1980)
This thesis is concerned with the study of cavitation behaviour of two-phase superplastic alloys, using mainly a hot microhardness technique. Cavitation is a serious problem in copper and iron base alloys, it drastically limits the elongation to failure and may affect the service properties of superplastically formed components. There is some empirical evidence to suggest that, for cavitation to occur, the two phases involved must be 'incompatible' that is, they show marked differences in certain properties. Ideally, this phenomenon would be investigated directly by an in-situ study of the deformation behaviour of each phase separately in the microduplex alloy at the superplastic temperature and hence pinpointing the phase incompatibilities, but existing techniques do not allow for this. Here, a hot microhardness tester was commissioned and used to determine the hardness and activation energy of each phase in-situ in a duplex alloy in thc superplastic temperature range. Zn/Al eutectoid and 60/40 brass were here used as models to represent a non-cavitating and cavitating class of superplastic alloys. In addition, a series of alloys were produced of compositions corresponding to those of the individual phases in these systems over a supcrplastic temperature range. These alloys were hot tensile. tested to find the ductility and ten'fle strength of each phase of superplastic alloy. The hot hardness data was correlated with the hot tensile data for the alloys over the whole temperature range from 0.4 to 0.84 Tm. Variation of Young's modulus with temperature was determined by a vibration technique and activation energy calculated form LnH versus Tm plots for all the alloys. In 60; 40 brass, the amount E of -T cavitation decreased with an increase in temperatur% and this alloy gave a maximum elongation of ti 110 pct at 250°C 1,0.45 Trrj, but it still exhibited extensive cavitation. In the Zn/Al eutectoid, no cavitation was observed apart from that associated with a few large inclusions. The hardness values of the two phases in a/ß brass were very different at the superplastic temperature, as were the load extension curves from the tensile tests and the calculated activation energies. In. the Zn/Al eutectoid however, the mechanical properties of the two phases were similar, though the activation energies were different. Finally, an attempt was made to explain the occurrence of cavitation in Supral 150 and certain steels, in some cases experimentally and in others from data available in the literature.